PENGGUNAANSISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI DIY - , Evy Hariana; , Dr. Ir. Eko Nugroho, Msi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background:Hospital information systems have an important role to support clinical and administrative services. Management of information in hospitals have been using electronic-based information systems (SIMRS), especially to support management decision making. Nevertheless detail SIMRS utilization in Indonesia are not widely known. Objective:Toanalyzethe extent to whichthe use of hospital management information system in the DIY in support of patient care both administratively andclinically. Specific objectives: todescribe the characteristics ofthe use of hospital management information system in the DIY based onownership, describethe benefits and barriers to the implementation of a hospital information management system. Methods:This study was a descriptive study with a qualitative design, with the aim to analyze the use of hospital management information system in the province in support of patient care both administratively and clinically. Guide in search of this data by using questionnaires adapted from HIMSS. Results:A total of 82.21% RS DIY SIMRS already adopted the system. SIMRS used for the majority of the administrative functions in the form of electronic patient registration (79.17%) and billing system (70.83%). Although still little clinical functionality has been used for medical documentation (58.33%), electronic prescribing (22.92%), laboratory (39.58%), and pharmaceutical warehouse inventory system (60.42%). Conclusion:Characteristic use of hospital management information system in the province based on RS ownership that both administrative functions and clinical functionsat its use over many private hospitals. Hospitals generally agree with the perceived benefits with the implementation of theim proved efficiency and SIMRS intransaction activity. Human resource skills, availability of infrastructure and support aspects of the organizationis an obstacle in the implementation SIMRS DIY